THE IMPACT OF CERTAIN ANTHROPOMETRIC DIMENSIONS ON THE REALIZATION OF MOTOR ABILITIES IN KARATE ATHLETES - Shkelzen Shalja; Visar Ganiu; Zorica Stankovska; Žarko Kostovski (Sport Scientific And Practical Aspects, 2025)
The research was conducted on 37 senior karate athletes’ seniors, males, at the age of 18 to 30, competitors of inter- national rank. They are potential members of the Kosovo national team. Two test batteries were used on the sample of the respondents: 5 anthropometric variables as a predictor system and 13 basic motor variables as a criterion system. From previous studies it can be concluded that the longitudinal dimensionality of the skeleton and motor abilities, in particular, speed, explosive force, as well as coordination of movement play an important role in karate sport, especially for the competitors who participate in the discipline kumite. The research was conducted in order to determine the impact of the predictor system of variables on the success of the realization of the criterion variables. By applying Linear Regression Analysis, the connection of the predictors with certain motor tests was determined, i.e. their prediction was determined.